A Systematic Review of Resilience Factors for Psychosocial Outcomes During the Transition to Adulthood Following Childhood Victimisation. (April 2023) - Latham, Rachel M.; Newbury, Joanne B.; Fisher, Helen L.
Exposure to childhood victimisation (i.e. abuse, neglect, domestic violence or bullying) can detrimentally impact later psychosocial adjustment. However, this is not the case for all victimised children; some do well despite their experiences and are considered to be resilient. Understanding the factors associated with such resilience is important to inform interventions to support better psychosocial outcomes among victimised children. This review provides an overview of the extant research examining resilience factors for psychosocial outcomes during the transition to adulthood following exposure to childhood victimisation. Studies were identified through a systematic literature search of Embase, PsychINFO and Ovid MEDLINE databases. The 26 included studies spanned a range of psychosocial outcomes between ages 18–25, including education and work, housing and independent living, criminal behaviour, victimisation, and social and psychological adjustment. For each outcome, a variety of putative resilience factors had been investigated including those related to the individual, their family and the wider community within which they lived. However, because few studies had comparable resilience factors and psychosocial outcomes, it is difficult to draw conclusions about which factors are consistently associated with resilience to a particular psychosocial outcome. Additionally, this review revealed that the included studies were of variable methodological quality – many were limited by cross-sectional designs with retrospective self-reports of childhood victimisation, and convenience or unrepresentative samples. In this review, we also highlight gaps in knowledge about the co-occurring impact of multiple resilience factors in combination and the need for studies conducted in non-Western and low- and middle-income countries.